PENGARUH PENDEKATAN GAMIFICATION BERBASIS EDUCAPLAY TERHADAP HASIL BELAJAR IPAS PESERTA DIDIK KELAS V SEKOLAH DASAR - Melvinosa, Cheza; Nurwahidin, Muhammad; Herpratiwi; Dian Putra, Agung (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem of this research is the low learning outcomes of fifth-grade students of SD Negeri 2 Reno Basuki in science. The research aims to, first, determine the effect of the educaplay-based gamification approach in science learning on student learning outcomes. Second, determine the effect of the quizizz-based gamification approach in science learning on student learning outcomes. Third, determine the difference in the improvement of science learning outcomes in the experimental class and the control class in students. The research method uses a quasi-experimental design with a nonequivalent control group design. The research population is all fifth-grade students totaling 47 students. The research sample was determined by cluster random sampling technique. Data collection techniques use tests and non-tests. Hypothesis testing uses paired sample t-tests and independent samples t-tests. The results of the study, first, there is an effect on the application of the educaplay-based gamification approach on science learning outcomes with a significance value of p = 0.000 or 0.000 < 0.05. Second, there is an influence on the application of the quizizz-based gamification approach on the results of learning science with a significance value of p = 0.000 or 0.000 < 0.05. Third, there is a difference in the increase in the results of learning science in the experimental class that uses the educaplay-based gamification approach with the control class that uses the quizizz-based gamification approach in grade V elementary school students with a significance value of p = 0.028 or 0.028 < 0.05.